Types Of Practical Graphics And Its Place In The System Of Continuous Education (Journal of Architectural Design, 2024)
In computer graphics, computers are used as a means of creating images, as well as for processing visual data obtained in one way or another and stored on a computer. Types of applied graphics and its place in the continuing education system, including the purpose and tasks of applied graphics.